Gipertekst kak lingvističeskoe proâvlenie globalizacii - Čbmerkin, Sergej G. (Stylistyka, 2020)
This article is about hypertext as a phenomenon directly imbedded in globalization. The dynamie development of various nonlinear processes has led to the active development of non-linearity in language. This is most evident in the linguistic unit of the hypertext. In particular, the electronic hypertext reveals features that have never before existed in language, making the classification and regulation of these features at th s stage o f language leaming impossible, as the traditional definition o f standards is based on a linear language level, and hypertext, a complicated non-hnear formation, with the signs o f other semiotic systems, in other languages, etc.